Síntese, caracterização e avaliação das atividades antimicrobianas e anti-inflamatória de derivados de fenilpropanóides e benzofenona - Folquitto, Laís Regina Dos Santos (2022)
As a branch of organic chemistry, organic synthesis makes the basis of medicinal chemistry, whose central objective is planning and synthesis of biologically active substances. Our research group has worked on the study, planning and synthesis of new substances from eugenol and its analogues, as well as benzophenones. Both are substances originally obtained from natural products and are reported in the literature with the most varied biological activities. This study is divided into two chapters, in which the first presents the synthesis, characterization and in vivo evaluation of the anti-inflammatory potential of benzophenone- based O-glucosides. In this chapter is described the synthesis of peracetic and deacetylated O- glucosides, derivatives of 2,4-dihydroxybenzophenone and 4-hydroxy-4'- methoxybenzophenone in which the anti-inflammatory potential was determined by an ear edema assay in rats, induced by croton oil. The evaluated substances shows statistically significant edema inhibition equivalent to the reference drugs. The second chapter presents an attempt to synthesis of 5-mercapto-1,2,4-triazole and 1,3,4-thiazine derivatives, as well as the synthesis, characterization and in vitro evaluation of antibacterial, antifungal, antimycobacterial and anti-Trypanosoma cruzi activities of thiazole derivatives of eugenol, dihydroeugenol, O-vanillin and salicylaldehyde, which were characterized by the usual methods (M.P., I.R., NMR, and MS). Bactericidal and antibiofilm activities of thiazole derivatives were also evaluated from the values of minimum inhibitory concentrations (MICs) obtained in the microdilution assay. Thiazole derivatives containing donor groups of electronic density as substituters, reveal potential activity against different species of fast-growing mycobacteria (M. abscessus, M. massiliense, M. fortuitum e M. smegmatis). The evaluated derivatives have bactericidal activity in their MICs up to 24 hours, determined by the time-kill kinetic curves, as well as inhibition activity of biofilm formation, showing low or no cytotoxicity observed against PBMC (peripheral blood mononuclear cells) and Vero cells.